FARMER’S BARRIERS IN USING INNOVATIVE TECHNOLOGY TO PROMOTE AGRICULTURAL PRODUCTS IN BATU CITY (A PERSPECTIVE FROM THE COMMUNITY DEVELOPMENT ACTORS) - Alia Fibrianingtyas; Mas Ayu Ambayoen (Socio-Economics/Agribusiness Department, 2024)
Changes in extension in the era of the industrial revolution 4.0 have greatly influenced the way information is delivered to farmers towards providing a more dynamic flow of information. This open access to information is the result of the effects of the use of information and communication technology, especially advances in cell phones and the internet. Information and communication technologies in agricultural development require certain educational processes and capacity building due to some technical difficulties and lack of skills to apply it. However, the smart city concept that implementing in Batu City in fact has not been successful. So, the objective of this research is to identify the obstacles of farmers in using innovative technology to promote the agricultural products. This research is using qualitative method with the data analysis method using Miles and Hubberman. The data was collected from indepth interview to extention workers. The results of this research shows that there are three obstacles that affects the utilization of innovative technology, such as farmer’s capability, management of application, and features of application complexity.